Comparison of Percutaneous Transforaminal Endoscopic Discectomy and Microscope‐Assisted Tubular Discectomy for Lumbar Disc Herniation. Issue 5 (10th June 2021) - Liu, Lantao; Xue, Hui; Jiang, Lianghai; Chen, Hao; Chen, Longwei; Xie, Siyu; Wang, Dechun; Zhao, Mingwei
Abstract : Objective: The aim of the present study was to compare the clinical outcomes and quality of life following percutaneous transforaminal endoscopic discectomy (PTED) and microscope‐assisted tubular discectomy (MTD) for lumbar disc herniation (LDH). Methods: This study had a retrospective design. From June 2017 to June 2018, the clinical data of 120 patients with LDH treated with PTED (60 cases, PTED group) and MTD (60 cases, MTD group) were analyzed and followed up for at least 20 months. There were 59 men and 61 women. Patients were aged between 22 and 80 years. The operation time, intraoperative blood loss, incision length, frequency of intraoperative fluoroscopy, cost, hospital stay, types of herniated discs, complications, and clinical outcomes were evaluated. Clinical outcomes were assessed using the visual analog scale (VAS), the Oswestry disability index (ODI), and the modified Macnab criteria. Short‐Form 36 (SF‐36) and the EQ‐5D‐5L were used to evaluate the quality of life of patients. The data between the two groups were compared by independent sample t ‐tests. Multiple comparisons between samples were analyzed by analysis of variance. Results: Compared with the MTD group, the PTED group had shorter incision length (9.20 ± 1.19 mm vs 26.38 ± 1.82 mm), less intraoperative blood loss (18.00 ± 4.97 mL vs 39.83 ± 6.51 mL), and shorter hospital stay (5.42 ± 5.08 days vs 10.58 ± 3.69 days) ( P = 0.00). PTED was much more appropriate for foraminal and extraforaminal disc herniation. The incidence of paresthesia was lower in the PTED group (6.67% vs 16.67%). At each follow up, the VAS and ODI scores of all patients were significantly improved compared with those before surgery ( P = 0.00). At 3 days postoperatively, the lumbar VAS score of the PTED group was significantly lower (1.58 ± 1.00 vs 2.37 ± 1.10, P = 0.00). The excellent rate of the PTED group reached 91.67%, and that of the MTD group reached 93.33%. Compared with the preoperative SF‐36 scores for physiological function, mental health, and social function, the postoperative scores were significantly improved in both groups ( P = 0.00). The EQ‐5D‐5L in the PTED group increased from 0.30 ± 0.17 before the operation to 0.69 ± 0.13 after 6 months of follow up ( P = 0.00) and 0.73 ± 0.14 after 20 months of follow up. The EQ‐5D‐5L in the MTD group increased from 0.28 ± 0.17 before the operation to 0.68 ± 0.13 after a 6‐month follow up ( P = 0.00), and 0.73 ± 0.12 after a 20‐month follow up. Conclusion: Although both PTED and MTD are effective for LDH, PTED is much more appropriate for various types of LDH and has the advantages of the low incidence of low back pain, fewer complications, and early recovery. Abstract : Schematic illustration